2022
DOI: 10.1101/2022.11.18.517156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 exposure in Norway rats (Rattus norvegicus) from New York City

Abstract: Millions of Norway rats (Rattus norvegicus) inhabit New York City (NYC), presenting the potential for transmission of SARS-CoV-2 from humans to rats and other wildlife. We evaluated SARS-CoV-2 exposure among 79 rats captured from NYC during the fall of 2021. Results showed that 13 of 79 rats (16.5%) tested IgG or IgM positive, and partial genomes of SARS-CoV-2 were recovered from four rats that were qRT-PCR positive. Using a virus challenge study, we also showed that Alpha, Delta, and Omicron variants can caus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Thus, based on the similarities of Angiotensin Converting Enzyme 2 (ACE2) and Transmembrane Protease, Serine 2 (TMPRSS2), both recognized as receptors and protease for the SARS-CoV-2 spike protein, wild rodents were proposed as having a high potential risk of infection by this virus 15 . However, empirical evidence obtained in a previous study 7 and in this study suggests that urban wild rodents, such as the M. musculus and R. norvergicus, have a low rate of SARS-CoV-2 infection. Here, we found that 12.1% of M. musculus and 5.8% of R. norvegicus were infected with SARS-CoV-2.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Thus, based on the similarities of Angiotensin Converting Enzyme 2 (ACE2) and Transmembrane Protease, Serine 2 (TMPRSS2), both recognized as receptors and protease for the SARS-CoV-2 spike protein, wild rodents were proposed as having a high potential risk of infection by this virus 15 . However, empirical evidence obtained in a previous study 7 and in this study suggests that urban wild rodents, such as the M. musculus and R. norvergicus, have a low rate of SARS-CoV-2 infection. Here, we found that 12.1% of M. musculus and 5.8% of R. norvegicus were infected with SARS-CoV-2.…”
Section: Discussioncontrasting
confidence: 55%
“…Here, we found that 12.1% of M. musculus and 5.8% of R. norvegicus were infected with SARS-CoV-2. In a study performed with 79 R. norvegicus captured in New York City during the fall of 2021, showed that 16.5% had titers of IgG-or IgM-positive for SARS-CoV-2 and four rats (5%) were RT-qPCR positive 7 . Another study performed with 80 R. norvegicus and 69 mice (Apodemus sylvaticus) trapped in an urban park and sewage treatment facility in Liverpool, UK, showed that seven rats (8.7%) had positive titers of IgA in lung tissue fluid 8 , whereas in two of 213 (0.9%) thoracic cavity fluid samples of R. norvegicus from Windsor, Canada, neutralizing antibodies against SARS-CoV-2 were identified 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were collected from the wastewater system. SARS-CoV-2 viral RNA was found in them [ 44 ]. It is now well established in the literature that both species jump and species regression occurs in SARS-CoV-2 transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The turbinate was homogenized in 1 ml of the same medium. The debris were pelleted by centrifugation for 10 min at 12,000 × g. Their infectious virus titers were determined by TCID50 with MDCK cells (for influenza viral titers) or Vero E6 cells (for SARS-CoV-2 viral titers) as previously described (64,65).…”
Section: Infectious Viral Titration By Tcid50mentioning
confidence: 99%